The Idea of Structuring National Legislation Based on The Ratio of Decidendi & Obiter Dictum Constitutional Court Decision: Gagasan Penataan Legislasi Nasional Berbasis Ratio Decidendi dan Obiter Dictum Putusan Mahkamah Konstitusi - Hakiki, Yuniar Riza; Taufiqurrahman, Taufiqurrahman (Jurnal Konstitusi, 2023)
MK decission which are "rejecting" and "unacceptable", often contain a constructive “ratio decidendi/obiter dictum” to the formation of the UU, but has not been effectively acted upon in the Prolegnas. This study analyzes: (1) the urgency of national legislation arrangements based on the ratio decidendi/obiter dictum; (2) the formulation of national legislation arrangements based on the ratio decidendi/obiter dictum. This normative research concludes: (1) UU must be formed based on the constitution, but the constitutional messages/guidelines in the MK’s legal considerations-that impactful on the substance of the UU are not followed up. (2) revise Article 18 of the Law No.12 of 2011 as ammanded through the Law No.13 of 2022 on the Establishment of Law and Regulation; give priority weight-to the law affected by the MK decision and include in the Prolegnas priority; the substance of the MK decision must be followed up in the drafting; and institute constitutional dialogue.